Real-Time Single-Molecule Studies of RNA Polymerase–Promoter Open Complex Formation Reveal Substantial Heterogeneity Along the Promoter-Opening Pathway - Malinen Anssi M.; Bakermans Jacob; Aalto-Setälä Emil; Blessing Martin; Bauer David L.V.; Parilova Olena; Belogurov Georgiy A.; Dulin David; Kapanidis Achillefs N. (Academic Press, 2022)
The expression of most bacterial genes commences with the binding of RNA polymerase (RNAP)–σ70 holoenzyme to the promoter DNA. This initial RNAP–promoter closed complex undergoes a series of conformational changes, including the formation of a transcription bubble on the promoter and the loading of template DNA strand into the RNAP active site; these changes lead to the catalytically active open complex (RPO) state. Recent cryo-electron microscopy studies have provided detailed structural insight on the RPO and putative intermediates on its formation pathway. Here, we employ single-molecule fluorescence microscopy to interrogate the conformational dynamics and reaction kinetics during real-time RPO formation on a consensus lac promoter. We find that the promoter opening may proceed rapidly from the closed to open conformation in a single apparent step, or may instead involve a significant intermediate between these states. The formed RPO complexes are also different with respect to their transcription bubble stability. The RNAP cleft loops, and especially the β′ rudder, stabilise the transcription bubble. The RNAP interactions with the promoter upstream sequence (beyond −35) stimulate transcription bubble nucleation and tune the reaction path towards stable forms of the RPO.